Radiosensitivity Levels of In Vitro Cultured Celosia cristata Planlets by γ - Ray Irradiation - Hayati, Dhieni; Aisyah, Syarifah Iis; -, Krisantini (Journal of Tropical Crop Science, 2016)
Plantlets of the ornamental plant Celosia cristata were irradiated with gamma rays to increase their genetic diversity. This study was aimed to establish  the lethal levels of gamma radiation  (LD20, LD30 and LD50) for  C. cristata plantlets.   The irradiation doses used were 0, 25, 50 and 75 Gy. The growth of irradiated plantlets was evaluated to the third generation. Irradiated C. cristata MV1 plantlets showed a decrease in growth, with plantlets irradiated at 75 Gy showing only 30% survival.   Abnormal growth characteristics observed  in the  third generation plantlets included  the shortening of internodes, and curling of leaves.  LD50, LD30 and LD20 of C. cristata were 68.73 Gy, 46.68 Gy and 35.65 Gy, respectively.